Religion som strømme i en flydende bevidsthed - Schjødt, Uffe (Religionsvidenskabeligt Tidsskrift, 2005)
Archaeologist Steven Mithen claims to show how and why the human mind developed into a culturally capable entity. By adopting the notion of the ontogenetic recapitulation of phylogeny, Mithen integrates several different perspectives on developmental psychology with the state of the art of archaeological data. According to Mithen the mind has undergone some important changes during the last couple of million years ending with what Mithen calls Cognitive Fluidity. A cognitively fluid mind is the only architecture that allows abstract thinking and use of symbols. This article, however, argues that Mithen’s cognitive approach suffers from important theoretical inconsistencies, since much of the research involved seem to contradict each other. Thus psychologist Howard Gardner’s multiple intelligence theory does not fit well into philosopher Jerry Fodor’s theory of mind, while developmental psychologist Karmiloff-Smith’s developmental theory is interesting to Mithen only if recapitulation is accepted as a framework, and even then problems seem to exist between Mithen’s abrupt jump into a cognitively fluid mind about 40,000 years ago and Karmiloff-Smith’s domain specific developmental stages. In my view, Steven Mithen’s Book, The Prehistory of the Mind does not offer a satisfying account of how the mind finally went fluid and became able to perform complex artifacts and religious behaviour.